Morfometría de polinios y crecimiento del tubo polínico en Oxypetalum balansae y O. solarroides - Riccardo, María Laura; Facciuto, Gabriela Rosa; Bugallo, Veronica Lucia (Sociedad Argentina de Botánica, 2026)
Poster